5′ flanking sequence of the human immediate early responsive gene ccn1 (cyr61) and mapping of polymorphic CA repeat sequence motifs in the human ccn1 (cyr61) locus. Issue 3 (1st June 2001) - Schütze, N; Rücker, N; Müller, J; Adamski, J; Jakob, F
Abstract : Aims —The human ccn1 (hccn; hcyr61) gene has been identified previously at the mRNA and protein level as a 1, 25-dihydroxyvitamin D3 and growth factor regulated gene in human osteoblasts. This study aimed to analyse genomic clones containing the human ccn1 (cyr61) gene and to provide the 5′ flanking region. Methods —Genomic clones were isolated by screening a λ library and by array filter hybridisations of a genomic library. Sequencing was performed using the dye terminator method. Promoter activity was measured after transient transfection using a β galactosidase assay. CA repeat motifs were studied by a combined PCR/fragment analysis protocol. Results —The human 5′ flanking region of 870 nucleotides contains several stretches with high homology to the mouse promoter as well as CA repeat motifs. This first report on the human 5′ flanking sequence of the hccn1 (hcyr61) gene provides important insights into regulation pathways for the expression of this 1, 25-dihydroxyvitamin D3 and growth factor responsive early gene. A genomic clone containing the hccn1 (hcyr61) gene region also yielded a CA sequence located 3′ of the ccn1 (cyr61) gene. This CA repeat and one of the CA repeat motifs in the promoter were studied in detail and found to be polymorphic. Conclusions —The 5′ flanking sequence of the hccn1 (hcyr61) gene provides insights into the mechanisms of regulation of this immediate early gene product. The CA repeat polymorphisms within the gene region will be useful in the genetic study of disorders affecting bone metabolism.